Instagram untuk Caleg Lokal: Bagaimana Dua Caleg Muda DPRD Tangerang Membangun Personal Branding di Era Digitalisme Politik - Megi Primagara (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
This study explores how young legislative candidates at the local level utilize Instagram as a campaign medium in the era of political digitalism. The focus is on two DPRD candidates in Tangerang City during the 2024 election in Electoral District 3 (Cipondoh–Pinang): Muhamad Azka Nur Fauzi from the National Mandate Party and Ashma Nafilah Maulida from the Prosperous Justice Party. Employing a qualitative descriptive approach and in-depth interviews with key informants, this research analyzes their personal branding strategies using Peter Montoya’s eight laws of personal branding.  The findings reveal that despite their relatively small number of followers, both candidates successfully built authentic and community-relevant political images. MANF emphasized UMKM development and religiosity, aligning with his personal background, while ANM highlighted humanistic social programs and her unique writing hobby. Nevertheless, both still showed weaknesses in several of Montoya’s principles, particularly distinctiveness and visibility consistency. The study concludes that Instagram is not merely a low-cost promotional tool but a strategic platform for local candidates to foster public trust, provided their personal branding remains authentic, consistent, and responsive to local needs.